Impact of refractive index increment on the determination of molecular weight of hyaluronic acid by muti-angle laser light-scattering technique - Ying Han (Nature Portfolio, 2020)
Abstract Hyaluronic acid (HA) is applied in a number of medical applications and HA of different molecular weight (Mw) are used in different pharmaceutical preparations. In determination of Mw by muti-angle laser light-scattering (MALS), refractive index increment (dn/dc) is an important parameter for accuracy. Herein, the influence of dn/dc on the Mw of HA in stroke-physiological saline solution is investigated by MALS in this work. Additionally, the Mw variation of HA in the manufacturing process of preparations is measured. It is shown that each HA sample corresponds to a specific value of dn/dc, which is varied from 1.38 to 1.74 L/g with the Mw increasing from 13.5 to 2840 kDa in solution. It is indicated by the results from both MALS approach and viscometry that appropriate dn/dc should be selected for Mw determination. In steam sterilization process of preparations at 121 °C, the Mw and conformation of HA can be accurately and rapidly determined by MALS. This work provides a precise method to determine the Mw of HA in the medical applications and preparation industries.